Algebra 4 course - Barrouk Bachir (university of Souk Ahras, 2025)
This course aims to provide a comprehensive understanding of key concepts in linear algebra and their applications to more advanced structures in vector spaces. It is designed to build a solid theoretical foundation while preparing students to work with practical problems involving bilinear forms, matrix theory, and spectral analysis